2013
DOI: 10.1155/2013/615281
|View full text |Cite|
|
Sign up to set email alerts
|

Spirometry in Primary Care

Abstract: Canadian Thoracic Society (CTS) clinical guidelines for asthma and chronic obstructive pulmonary disease (COPD) specify that spirometry should be used to diagnose these diseases. Given the burden of asthma and COPD, most people with these diseases will be diagnosed in the primary care setting. The present CTS position statement was developed to provide guidance on key factors affecting the quality of spirometry testing in the primary care setting. The present statement may also be used to inform and guide the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 22 publications
0
45
1
5
Order By: Relevance
“…1 Ei- Figure 3 shows a sample spirometry report for pre-and post-bronchodilator studies, as suggested by the Canadian Thoracic Society. 85 Only the FEV 1 , FVC, and FEV 1 /FVC are reported. Both the lower limit of normal and percent of predicted are displayed for pre-bronchodilator measurements.…”
Section: Performance Of Spirometry In Primary Carementioning
confidence: 99%
“…1 Ei- Figure 3 shows a sample spirometry report for pre-and post-bronchodilator studies, as suggested by the Canadian Thoracic Society. 85 Only the FEV 1 , FVC, and FEV 1 /FVC are reported. Both the lower limit of normal and percent of predicted are displayed for pre-bronchodilator measurements.…”
Section: Performance Of Spirometry In Primary Carementioning
confidence: 99%
“…Post bronchodilator improvement in FEV 1 can document the degree of reversibility of airway obstruction. All these tests are widely available and well standardized [32,33]. Forced expiratory flow between 25 and 75% of vital capacity (FEF ) is considered to reflect small airways obstruction, but it is more variable.…”
Section: Physiological Measuresmentioning
confidence: 99%
“…The test consisted of maximal inspiratory and expiratory maneuvers, which were conducted in the device, until it was possible to register three reproducible maneuvers according to the recommendations 8 . All of the tests were conducted in a climatized environment, by means of previously calibrated PFT KoKoÂź spirometer.…”
Section: Spirometrymentioning
confidence: 99%